La lectura creativa: propuestas para fortalecer la expresión escrita - Nayibe Tabash-Blanco (Revista Electrónica Educare)
Writing is a process that allows expressing and communicating ideas. Its main objective is the construction of meanings. This article underscores the importance that reading has as a means of strengthening writing skills. In doing so, it promotes in the elementary school students their imagination, critical thinking and creativity.